Camera, Canvas, and Qibla: Late Ottoman Mobilities and the Fatih Mosque Painting - Göloğlu, Sabi̇ha (Muqarnas, 2021)
Abstract This article discusses the multiple mobilities of images, photographs, photographers, viewers, and places by focusing on Miʿmarzade Muhammed ʿAli’s (d. 1938) oil-on-canvas painting, now located in the Fatih Mosque in Istanbul. It explores the limits, lives, possibilities, and uses of photographic views and the exchanges between photography, painting, and print media by investigating the geopolitics and geopiety of the Hamidian era (i.e., Sultan ʿAbdülhamid II, r. 1876–1909), the production and circulation of early photographs of Mecca and Medina, and the spatial tradition of qibla decorum. It examines the photographic oeuvres of Christiaan Snouck Hurgronje (d. 1936), al-Sayyid ʿAbd al-Ghaffar, and the committee of the Erkān-ı Ḥarbiyye (General Military Staff), including Muhammad Sadiq Bey (d. 1902), as well as the reproductions and changing contexts of these photographs. Furthermore, this article highlights the role of print media in the dissemination and mobilization of the photographic image and the malleable politics of representation, especially as it pertains to the two sacred cities of Mecca and Medina.